PELATIHAN PERAKITAN, INSTALASI DAN TROUBLESHOOTING KOMPUTER/LAPTOP PADA ANGGOTA ORGANISASI PMII KAB. BANJAR - Mirza Yogy Kurniawan; Fathul Hafidh; Al Fath Riza Kholdani (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2017)
Hardware and Software are the main elements in information technology one of which is the computer. The computer itself is divided into two forms namely the type of portable or called laptop and Personal Computer or called PC. Computers are divided into two types namely Built Up and Assembled. Computer assembly is a technique of assembling and installing all hardware components to become a computer that can be used as it functions. Computer installation is the process of installing software into the computer to be useful as usefulness, while troubleshooting is to solve problems that occur both in hardware and computer software. Therefore, this devotion has a purpose so that the participants have knowledge in assembling, installing and troubleshooting computer technology either in personal use or in the field of business. This devotion is implemented in PMII Kab. Banjar, about 10 members who can follow the implementation of Community Service Activities.